Investigating the Complex Association Between Viral Ecology, Environment, and Northeast Pacific Sea Star Wasting - Hewson, Ian; Bistolas, Kalia S. I.; Quijano Cardé, Eva M.; Button, Jason B.; Foster, Parker J.; Flanzenbaum, Jacob M.; Kocian, Jan; Lewis, Chaunte K. (Frontiers in Marine Science, 2018)
Sea Star Wasting Disease (SSWD) describes a suite of disease signs that affected > 20 species of asteroid since 2013 along a broad geographic range from the Alaska Peninsula to Baja California. Previous work identified the Sea Star associated Densovirus (SSaDV) as the best candidate pathogen for SSWD in 3 species of common asteroid (Pycnopodia helianthoides, Pisaster ochraceus and Evasterias troscheli), and virus-sized material (<0.22 µm) elicited SSWD signs in P. helianthoides. However, the ability of virus-sized material to elicit SSWD in other species of asteroids was not known. Discordance between detection of SSaDV by qPCR and by viral metagenomics inspired the redesign of qPCR primers to encompass SSaDV and two densoviral genotypes detected in wasting asteroids. Analysis of asteroid samples collected during SSWD emergence in 2013-2014 showed an association between wasting asteroid-associated densoviruses (WAaDs) and SSWD in only one species (P. helianthoides). WAaDs were found in association with asymptomatic asteroids in contemporary (2016 and later) populations, suggesting that they form subclinical infections at the times they were sampled. WAaDs were found in SSWD-affected P. helianthoides after being absent in asymptomatic individuals a year earlier at one location (Kodiak). Direct challenge of P. ochraceus, Pisaster brevispinus and E. troscheli with virus-sized material from SSWD-affected individuals did not elicit SSWD in any trial. RNA viral genomes discovered in viral metagenomes and host transcriptomes had viral loads and metagenome fragment recruitment patterns that were inconsistent with SSWD. Analysis of water temperature and precipitation patterns on a regional scale suggests that SSWD occurred following dry conditions at several locations, but mostly was inconsistently associated with either parameter. Semi-continuous monitoring of SSWD subtidally at two sites in the Salish Sea from 2013-2017 indicated that SSWD in E. troscheli and P. ochraceus was associated with elevated water temperatures, but wasting in P. helianthoides occurred irrespective of environmental conditions. Our data therefore do not support that widespread SSWD in species other than P. helianthoides is associated with potential viral pathogens. Rather, we speculate that SSWD may represent a syndrome of heterogeneous etiologies between geographic locations, between species, or even within a species between locations.